Environmental impacts of livestock in the developing world - Nicholson, Charles F.; Blake, R.W.; Reid, Robin S.; Schelhas, J. (Informa UK Limited, 2001)
This paper deals with the environmental impacts of livestock in the developing world. It discusses the complex role of livestock in developing countries, diversity of livestock production systems; health benefits from animal foods; livestock and the need for intensification; environmental impacts of livestock production; cattle and forest conversion in the Latin American tropics, impacts of livestock on biodiversity in sub-Saharan Africa; and livestock and greenhouse gas emission. The prinicples for assessing livestock systems in the developing world are outlined at the end of the paper.